2017
DOI: 10.1007/s00432-017-2397-3
|View full text |Cite
|
Sign up to set email alerts
|

SDHB-related pheochromocytoma and paraganglioma penetrance and genotype–phenotype correlations

Abstract: Purpose Succinate dehydrogenase subunit B (SDHB) gene mutations are associated with an aggressive clinical disease course of pheochromocytoma/paraganglioma (PHEO/PGL). Limited information is available concerning PHEO/PGL penetrance among SDHB mutation carriers with regards to primary tumor location, specific mutation type, and gender. We assessed PHEO/PGL penetrance in SDHB mutation carriers and described the clinical presentation and disease course. Methods Asymptomatic relatives (N=611) of 103 index patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 43 publications
4
65
2
5
Order By: Relevance
“…In their retrospective cohort analysis (index and non‐index patients) the penetrance was 24% at age 60 years . Males seem to be slightly more at risk than females of developing a PGL …”
Section: Phenotype Of Sdhx Mutation Carriersmentioning
confidence: 98%
See 1 more Smart Citation
“…In their retrospective cohort analysis (index and non‐index patients) the penetrance was 24% at age 60 years . Males seem to be slightly more at risk than females of developing a PGL …”
Section: Phenotype Of Sdhx Mutation Carriersmentioning
confidence: 98%
“…40 Males seem to be slightly more at risk than females of developing a PGL. 40,41 SDHB-related PGL/PCC are associated with a high risk of metastasis and poor prognosis. Earlier studies report a higher metastatic rate (31%-97%) [42][43][44][45] than more recent studies.…”
Section: Sdhb Mutationsmentioning
confidence: 99%
“…The importance of surveillance screening in asymptomatic relatives is highlighted when analysing studies that separate out the asymptomatic carriers/relatives from the index cases (Table ). These combined cohorts provide data on 1341 asymptomatic SDHB carriers and demonstrate a tumour detection rate of 15.4% (207 asymptomatic carriers with PPGLs identified on screening), when index cases are excluded (individual studies report a tumour detection rate ranging from 3.5% to 35%) . Penetrance estimates have fallen over time as more disease‐free asymptomatic carriers are identified.…”
Section: Surveillance Programmesmentioning
confidence: 99%
“…A review of the literature identified 13 manuscripts that attempted to address this issue. Eight studies argued for surveillance to start before or at 10 years including one expert opinion, three case series with less than five patients, three retrospective studies with 32, 92 and 116 patients, respectively), and one case‐control study with 241 patients . Three reports recommended starting from the second decade of life (one systematic review of 95 papers suggesting a start age between 11‐20 years, one retrospective study with 91 patients suggesting an age of 27.1 years based on HNPGL penetrance calculations and one case series of three families suggested a starting age of 18 years for HNPGL screening) .…”
Section: Methodsmentioning
confidence: 99%